Investigation of the physicochemical factors affecting the in vitro digestion and glycemic indices of indigenous indica rice cultivars - Indira Govindaraju; Anusha R. Das; Ishita Chakraborty; Sib Sankar Mal; Bhaswati Sarmah; Vishwa Jyoti Baruah; Nirmal Mazumder (Scientific Reports)
Abstract Rice (Oryza sativa) is a vital food crop and staple diet for most of the world’s population. Poor dietary choices have had a significant role in the development of type-2 diabetes in the population that relies on rice and rice-starch-based foods. Hence, our study investigated the in vitro digestion and glycemic indices of certain indigenous rice cultivars and the factors influencing these indices. Cooking properties of rice cultivars were estimated. Further, biochemical investgations such as amylose content, resistant starch content were estimated using iodine-blue complex method and megazyme kit respectively. The in vitro glycemic index was estimated using GOPOD method. The rice cultivars considered in our study were classified into low-, intermediate-, and high-amylose rice varieties. The rice cultivars were subjected to physicochemical characterization by using Fourier transform infrared (FTIR) spectroscopy and differential scanning calorimetry (DSC) techniques. FTIR spectral analysis revealed prominent bands at 3550-3200, 2927-2935, 1628-1650, 1420-1330, and 1300-1000 cm−1, which correspond to –OH groups, C=O, C=C, and C–OH stretches, and H–O–H and –CH bending vibrations, confirming the presence of starch, proteins, and lipids. Additionally, the FTIR ratio R(1047/1022) confirmed the ordered structure of the amylopectin. DSC analysis revealed variations in the gelatinization parameters, which signifies variations in the fine amylopectin structures and the degree of branching inside the starch granules. The percentage of resistant starch (RS) ranged from 0.50–2.6%. The swelling power (SP) of the rice flour ranged between 4.1 and 24.85 g/g. Furthermore, most of the rice cultivars are classified as having a high glycemic index (GI) based on the estimated in vitro GI (eGI), which varies from 73.74–90.88. The cooking properties of these materials were also investigated. Because the amylose content is one of the key factors for determining the cooking, eating, and digestibility properties of rice, we investigated the relationships between the amylose content and other biochemical characteristics of rice cultivars. The SP and GI were negatively correlated with the amylose content, whereas the RS had a positive relationship. The findings of our study can be beneficial in illustrating the nutritional profile and factors affecting the digestibility of traditional rice cultivars which will promote their consumption, cultivation, and contributes to future food security.